Multinational entities and transfer pricing disclosures - Sivabala, Rasarathnam (2022)
Globalisation opened new ways for companies to find ways to mitigate and/or avoid tax. Aggressive or abusive transfer pricing methods is one of the main tax avoidance practices engaged by multinational enterprises (“MNEs”). Following the request by G7, the Organisation for Economic Co-operation and Development (“OECD”), published Base Erosion and Profit Shifting (“BEPS”) report in 2015 on the fifteen-action plans to tackle aggressive and abusive tax avoidance practices and three of these focussed on transfer pricing matters. Although the International Accounting Standard’s Boards’ Conceptual Framework requires that the financial statements provide useful information for the financial statement readers, the relevant standards do not require MNEs to provide transfer pricing related disclosures. This study observed thirty listed MNEs, comprising of the top fifteen MNEs from Bursa Malaysia and the top fifteen MNEs from London Stock Exchange listings. The study found that most of the sample MNEs included some transfer pricing related disclosures in the annual reports but this was mainly restricted to confirmation that the related party transactions were at arm’s length. The study also found that there was significant difference between the disclosures provided by Malaysian and the UK MNE samples. However, there were no significant differences between the number of MNEs including a transfer pricing disclosure in 2020 compared to 2016. In addition, firm size, the presence of a higher proportion of independent non-executive directors on the board, CEO duality, total number of overseas subsidiaries and proportion of overseas subsidiaries within the group had a positive impact on the transfer pricing disclosure. This study provides insight for IASB & IRB on the current practice by MNEs and whether IASB should consider reviewing their guidance in relation to transfer pricing issues from an accounting perspective. GRI 207 which came into force in January 2021, provides guidance on transfer pricing disclosures for tax transparency reporting. Future studies could expand on this study to observe how the MNEs comply with the new requirement.